At the bottom of the sea... (Journal of Parents and Teachers, 2024)
At times, we only associate physical exercise with sports, but there are other much more enjoyable forms. When we were kids, we spent hours outdoors playing, running, and having fun with our friends. Games like "el pañuelo" also required some organization, encouraging structured play.